Nowhere to hide: unconventional translation yields cryptic peptides for immune surveillance. Issue 1 (20th June 2016) - Starck, Shelley R.; Shastri, Nilabh
Summary: Effective immune surveillance by CD8 + cytotoxic T cells of intracellular microbes and cancer depends on the antigen presentation pathway. This pathway produces an optimal peptide repertoire for presentation by major histocompatibility (MHC) class I molecules (pMHCs I) on the cell surface. We have known for years that the pMHC I repertoire is a reflection of the intracellular protein pool. However, many studies have revealed that pMHCs I present peptides not only from precursors encoded in open‐reading frames of mRNA transcripts but also cryptic peptides encoded in apparently 'untranslated' regions. These sources vastly increase the availability of peptides for presentation and immune evasion. Here, we review studies on the composition of the cryptic pMHC I repertoire, the immunological significance of these pMHC I, and the novel translational mechanisms that generate cryptic peptides from unusual sources.